Nama-Japa: Prayer of the Name in the Hindu and Christian Traditions - Kadankavil, T (Journal of Dharma, 1984)
Sister Vandana Näma-Japa: Prayer of the Name in the Hindu and Christian Traditions Bharatiya Vidya Bhavan, Bombay, 1984, pp. 308, Rs. 40/-